Pengaruh Penggunaan Afo Fleksibel Terhadap Keseimbangan Dinamis Pada Hemiparetic Cerebrovascular Accident (CVA) - Nur Rachmat; Agus Seto Nugroho; M Syafii (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background: Stroke or Cerebrovascular Accident (CVA) is a primary neurologic problem in the United States and in the World. There are approximately 2 million people surviving from strokes that have a disability of 40% need help in daily activities (Brunener & Suddarth, 2002). The restoration of the functioning of the limbs and the ability to move within a community is a top priority for individual adoption after experiencing CVA. Ankle Foot Orthosis (AFO) can be used by someone with a CVA hemiparetic to help restrain ambulation abilities. AFO can prevent drop foot, controls the ankle in the coronal and sagittal areas during standing and walking and improves the stability of the knee during ambulation. Method: This research use cross sectional study method to find out what happened now by using correlative design design research. The researcher discusses the strength of the relationship between variables that is dynamic balance in drop foot because CVA, when using AFO Flexible. This data is obtained from direct measurement of dynamic balance of Flexible AFO users using Time up and go Test. Results :Differences in the effect of AFO on the dynamic balance of Hemiaretic Cerebrovascular Accident (CVA) patients in the intervention and control group. The results showed the average dynamic balance of hemiaretic cerebrovascular accident patients in the intervention group (28.20) while the mean equilibrium was maintained in the control group (12.80). The result of statistical test with man whitney showed p value 0,000 <0,05 so there was difference of influence of AFO use to dynamic balance of Hemiaretic Cerebrovascular Accident (CVA) patient in intervention group and control group. This means that the more frequently the patient uses AFO in daily activities it can improve the optimal dynamic balance and can perform activities independently. Conclusion: There is a difference in the effect of AFO on the dynamic balance of Hemiaretic Cerebrovascular Accident (CVA) patients in the intervention and control group with p value 0,000 <0.05.